The Effect of Digital-Based Training on Employee Loyalty with Job Satisfaction as an Intervening Variable at the Sidikalang Sub-district Office, Dairi Regency - Fahreja S. Anjas Ujung; Abdi Sugiarto; Hernawaty (CV. Doki Course and Training, 2026)
The rapid development of digital technology has encouraged public sector organizations to adopt digital-based training as a strategic instrument in improving the quality of human resources. In addition to playing a role in improving employee competence, digital-based training is also expected to be able to influence employee attitudes, especially job satisfaction and employee loyalty. This study aims to analyze the effect of digital-based training on employee loyalty with job satisfaction as an intervening variable at the Sidikalang District Office, Dairi Regency. This study uses an associative quantitative research design. The research population includes all employees of the Sidikalang District Office which totals 47 people. Using census techniques (saturated sampling), as many as 40 employees were designated as research respondents. Data was collected through a structured questionnaire and analyzed using the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS) with the help of SmartPLS software version 3.3.3. The results of the study show that digital-based training has a positive and significant effect on employee loyalty, which indicates that an effective digital training program is able to directly strengthen employee commitment and attachment to the organization. In addition, digital-based training has also been proven to have a positive and significant effect on job satisfaction, which shows that flexibility, ease of access, and suitability of training materials with job needs can increase employees' positive perception of their work. However, job satisfaction does not have a significant effect on employee loyalty. Furthermore, job satisfaction has also not been shown to mediate the relationship between digital-based training and employee loyalty, suggesting that the influence of digital-based training on employee loyalty is directly dominant. The findings of this study indicate that in public sector organizations, employee loyalty can be directly increased through the design and implementation of effective digital-based training programs without having to rely on job satisfaction as an intervening mechanism. This research makes a theoretical and practical contribution to the development of human resource management by emphasizing the strategic role of digital-based training in strengthening employee loyalty to local government institutions.